Quantitative Optical Diffraction Tomography Imaging of Mouse Platelets - Stanly, Tess A.; Suman, Rakesh; Rani, Gulab Fatima; O’Toole, Peter J.; Kaye, Paul M.; Hitchcock, Ian S. (Frontiers in Physiology, 2020)
Platelets are specialized anucleate cells that play a major role in hemostasis following vessel injury. More recently, platelets have also been implicated in innate immunity and inflammation by directly interacting with immune cells and releasing proinflammatory signals. It is likely therefore that in certain pathologies, such as chronic parasitic infections and myeloid malignancies, platelets can act as mediators for hemostatic and proinflammatory responses. Fortunately, murine platelet function ex vivo is highly analogous to human, providing a robust model for functional comparison. However, traditional methods of studying platelet phenotype, function and activation status often rely on using large numbers of whole isolated platelet populations, which severely limits the number and type of assays that can be performed with mouse blood. Here, using cutting edge 3D quantitative phase imaging, holotomography, that uses optical diffraction tomography (ODT), we were able to identify and quantify differences in single unlabeled, live platelets with minimal experimental interference. We analyzed platelets directly isolated from whole blood of mice with either a JAK2V617F-positive myeloproliferative neoplasm or Leishmania donovani infection. Image analysis of the platelets indicates previously uncharacterized differences in platelet morphology, including altered cell volume and sphericity, as well as changes in biophysical parameters such as refractive index and dry mass. Together, these data indicate that, by using holotomography, we were able to identify clear disparities in activation status and potential functional ability in disease states compared to control at the level of single platelets.